Hubungan Kecerdasan Spiritual Dengan Gambaran Diri Pada Wanita Pasca Mastektomi Kanker Payudara - Tengku Srifhanie Yahya; Veny - Elita; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research was conducted to determine the correlation between spiritual intelligence and self-image in post mastectomy breast cancer women. The research used the correlation method with cross sectional approach. It was conducted by studying 30 respondents in Surgical Oncology Polyclinic of Arifin Achmad Hospital Pekanbaru using accidental sampling technique. The research used a questionnaire consisting of 27 questions for spiritual intelligence and 15 questions for self-image which already been tested for it's validity and reliability. The analysis was bivariate analysis using Chi Square test. The results showed that there was no correlation between spiritual intelligence and self-image within post-mastectomy breast cancer patients (p value 1,000 > 0,05). The results of this research is suggested to be used by the hospitals to improve their quality of service and procedure by using a holistic approach, which mean to observe the post-mastectomy patients from the biological, psychological, social and spiritual point of view so that negative self-image can be prevented. Keywords : mastectomy, self-image, spiritual intelligence